A plant glycoside microcapsule and its preparation method and application

By encapsulating plant glycosides (aginalcoside) extracts into microcapsules using natural wax coating technology, the stability and leakage problems of water-soluble glycosides in toothpaste are solved, and the dual effects of stability and rapid release are achieved.

CN118948633BActive Publication Date: 2025-02-18INFINITUS (CHINA) CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411456569.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively wrap and stabilize water-soluble glycoside substances, especially in versatile liquid environments such as toothpaste, which leads to their oxidation and leakage during storage and use.

Method used

Using natural wax as coating material, plant glycoside (glycoside) extract is encapsulated into microcapsules with core-shell structure through fluidized bed coating equipment, ensuring that the surface of the microcapsules is dense and has low permeability, and can resist the damage of stirring and friction. .

Benefits of technology

It improves the stability of plant glycoside (glycoside) extracts, avoids oxidative decomposition, extends the storage stability of toothpaste, and can quickly release active ingredients when brushing teeth, exert therapeutic effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118948633B_ABST
    Figure CN118948633B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of oral care materials, and specifically discloses a plant glycoside microcapsule and a preparation method and application thereof. The microcapsule is a core-shell structure, and the shell of the microcapsule is natural wax; the mass ratio of the core of the microcapsule to the shell of the microcapsule is 1: (0.3-0.7); the natural wax comprises a mixture of beeswax and carnauba wax in a mass ratio of 1: (0-0.2). The present invention uses natural wax as a coating material to encapsulate the plant glycoside extract to form a microcapsule, the microcapsule has a smooth surface, and the encapsulation is dense, which improves the stability of the glycoside substance, avoids the instability phenomenon such as oxidation and decomposition of its active ingredients, improves the stability of the plant glycoside extract in toothpaste, and makes the toothpaste containing the microcapsule have a longer storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oral care materials, and in particular relates to a plant glycoside microcapsule and a preparation method and application thereof. Background Art

[0002] Toothpaste is usually made of a mixture of various raw materials such as functional ingredients, abrasives, moisturizers, thickeners, foaming agents, preservatives, sweeteners, etc. The functional ingredients are generally fluoride, zinc citrate, chlorhexidine and other substances. At present, the functional ingredients from plants have been widely used in the field of toothpaste. Glycoside compounds, formerly known as "glycosides", are a class of biologically active compounds widely found in plants. Their chemical structure is formed by the combination of sugar or sugar derivatives with non-sugar substances, such as flavonoid glycosides, anthracene glycosides, anthocyanins, etc. However, most of the glycosides extracted from natural plants are easily oxidized and may also have incompatibility with other ingredients in the product, limiting their industrial application. In order to improve the stability of glycosides, these natural extracts can be encapsulated in microcapsules to avoid or slow down the oxidation and attenuation of their active ingredients.

[0003] WO 2008 / 015186 A1 discloses a pigment microcapsule added to toothpaste, which disperses water-insoluble pigment in oil and adds fumed silica to gel the oil to form a capsule core; molten wax, oil and titanium dioxide are mixed and added to a hot suspension composed of core materials, stirred and mixed, and quickly cooled to obtain a microcapsule. The microcapsule leaks pigments due to friction caused by brushing teeth. The pigments selected in this preparation method tend to be oil-soluble pigments, and water-soluble glycosides are not suitable for this method. CN102906238 A uses melamine formaldehyde or urea formaldehyde to encapsulate water-soluble active ingredients, which can be used in daily necessities including toothpaste. However, the raw materials for preparing this kind of microparticles are potentially toxic and environmentally unfriendly, and plastic microbeads are now gradually banned from use in cosmetics. WO 2019 / 117890 A1 discloses a method for preparing pH-sensitive microcapsules that can be used in daily chemical products. Shellac and hydroxypropyl methylcellulose derivatives or acrylate derivatives are used as wall materials, and a pH-sensitive microcapsule is produced by flow focusing technology. The microcapsule is formed by solidifying droplets ejected from a concentric nozzle containing an outer shell fluid chamber and an inner core fluid chamber. However, common toothpastes on the market are neutral or weakly alkaline, and this type of microcapsule is not suitable for encapsulating glycosides.

[0004] Most plant-derived glycosides are water-soluble, which poses certain challenges to the realization of their encapsulation technology. In particular, toothpaste systems contain a certain amount of surfactants, such as sodium lauryl sulfate, sodium lauroyl sarcosinate, and cocamidopropyl betaine, which make the toothpaste system amphiphilic to water and oil. Therefore, if the glycosides encapsulated in the microcapsules are to be prevented from leaking during the shelf life in an amphiphilic liquid environment such as toothpaste or the leakage is within an acceptable range, the coating material of the microcapsules must have a dense structure and extremely low permeability in this environment. In addition, in the production process of products such as toothpaste, stirring, homogenization and other processes are required, and the microcapsules must be able to resist the destructive effects of abrasives, surfactants, etc. during the stirring and shearing process. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a microcapsule.

[0006] A second object of the present invention is to provide a method for preparing microcapsules.

[0007] A third object of the present invention is to provide a toothpaste.

[0008] A fourth object of the present invention is to provide application of the above-mentioned microcapsules in oral care products.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] The first aspect of the present invention provides a microcapsule, wherein the microcapsule is a core-shell structure, and the shell of the microcapsule is natural wax; the mass ratio of the core of the microcapsule to the shell of the microcapsule is 1:(0.3~0.7); the natural wax comprises a mixture of beeswax and carnauba wax in a mass ratio of 1:(0~0.2).

[0011] Preferably, the natural wax comprises a mixture of beeswax and carnauba wax in a mass ratio of 1:(0.05-0.2). The present invention selects a mixture of beeswax and carnauba wax, the viscosity of which in a molten state is lower than 0.3 Pa·s, which can ensure that the molten natural wax flows continuously in the peristaltic tube and the nozzle, thereby achieving coating of the core material of the microcapsule using a fluidized bed coating device.

[0012] Preferably, the core of the microcapsule includes plant glycoside extract. Glycoside compounds, formerly known as glycosides, plant glycosides are plant glycosides. In the present invention, plant glycosides and plant glycosides refer to the same substance, hereinafter collectively referred to as: plant glycoside (glycoside) extract, which is an extract obtained from plants as raw materials through physical and chemical extraction and separation processes.

[0013] Preferably, the inner core of the microcapsule further comprises a filler and a disintegrant; the mass ratio of the plant glycoside extract, the filler and the disintegrant is 1:(1-1.25):(0.05-0.3).

[0014] Preferably, the raw material of the plant glycoside extract is selected from at least one of scutellaria baicalensis, honeysuckle, coptis chinensis, liquorice, fritillaria thunbergii, eupatorium, patchouli, tangerine peel, dried ginger, jujube, anemarrhena asphodeloides, phellodendron chinense, moutan bark, raw rehmannia root and ophiopogon japonicus.

[0015] When the microcapsules of the present invention are used in toothpaste, the microcapsules are damaged due to friction during brushing, and water or saliva enters the microcapsules from the damaged parts to disintegrate the disintegrant, thereby accelerating the damage of the microcapsules, thereby causing the plant glycoside extract components in the microcapsule core to be quickly released.

[0016] Preferably, the inner core of the microcapsule is a solid material.

[0017] Preferably, the disintegrant is selected from at least one of cross-linked carboxymethyl cellulose and carboxymethyl starch.

[0018] Preferably, the filler is selected from microcrystalline cellulose.

[0019] Preferably, the particle size of the microcapsule is 370-920 μm.

[0020] Preferably, the content of baicalin in the microcapsule is 5-6.3%.

[0021] Preferably, the coating weight gain in the microcapsule is 27.07% to 57.79%.

[0022] The second aspect of the present invention provides a method for preparing the microcapsule provided by the first aspect of the present invention, comprising the following steps:

[0023] S1: making the core material of the microcapsule into a pellet core;

[0024] S2: coating the pellet core with natural wax to obtain the microcapsule.

[0025] Preferably, the step S1 is: after mixing the core material including the plant glycoside extract with a solvent, adopting an extrusion spheronization method to make a pellet core; further preferably, the step S1 is: after mixing the core material including the plant glycoside extract, a filler and a disintegrant with a solvent, extruding spheronization, drying, and sieving to obtain the pellet core.

[0026] Preferably, the solvent is selected from water.

[0027] Preferably, the mesh aperture in the extrusion and spheronization step is 0.3-0.7 mm.

[0028] Preferably, in the extrusion and spheronization step, the extrusion rate is 5-10 rpm, the spheronization rate is 500-1500 rpm, and the spheronization time is 20-60 min.

[0029] Preferably, the particle size of the pellet core is 0.3-0.7 mm.

[0030] Preferably, the step S2 is: heating and melting the natural wax, and then coating the pellet cores with a fluidized bed coating device, and obtaining the microcapsules after cooling.

[0031] Preferably, the material temperature of the fluidized bed coating equipment is controlled at 25-40°C, the spray pressure is 0.1-0.2 MPa, the compressed air heating temperature is 150-200°C, the air inlet rate is 300-800 rpm, and the exhaust rate is 600-1200 rpm.

[0032] Preferably, the heating and melting temperature is 110-140°C.

[0033] Preferably, a centrifugal disc is provided in the fluidized bed coating equipment.

[0034] Preferably, the rotation speed of the centrifugal disk is 300-500 rpm. The present invention utilizes a fluidized bed coating device with a centrifugal disk, and the microcapsules are subjected to the combined effects of centrifugal force, friction force, and air intake buoyancy, so that the microcapsules are smoother and denser on the surface, have lower roughness, and have almost no gaps and cracks compared to the microcapsules obtained by traditional fluidized bed coating. They can resist friction and wear during the preparation of toothpaste products, and extend the storage stability of toothpaste containing the microcapsules.

[0035] The third aspect of the present invention provides a toothpaste, comprising the microcapsules provided by the first aspect of the present invention. The microcapsules in the present invention can be used in products such as toothpaste. In the production process of toothpaste and other products, stirring, homogenization and other processes are required. In this process, the microcapsules must resist the destructive effects of abrasives, surfactants and the like during the stirring and shearing process. Therefore, the microcapsules in the present invention can, on the one hand, achieve complete encapsulation of the plant glycoside extract by natural wax, and there can be no gaps in the shell of the microcapsule; on the other hand, the microcapsules in the present invention can quickly release active ingredients when subjected to brushing friction, thereby exerting the efficacy of the plant glycoside.

[0036] Preferably, the toothpaste is calcium carbonate toothpaste or silicon dioxide toothpaste. The microcapsules in the present invention have smooth surfaces and dense encapsulation, can be stable for a long time in the calcium carbonate and silicon dioxide toothpaste matrix, and can be broken and released when brushing teeth.

[0037] The fourth aspect of the present invention provides use of the microcapsule provided by the first aspect of the present invention in an oral care product.

[0038] The beneficial effects of the present invention are as follows: the present invention uses natural wax as a coating material to encapsulate plant glycoside extracts to form microcapsules, the surface of the microcapsules is smooth, the encapsulation is dense, the stability of the plant glycoside extracts is improved, the instability phenomena such as oxidation and decomposition of glycoside components are avoided, the stability of the plant glycoside extracts in toothpaste is improved, and the toothpaste containing the microcapsules has a longer storage stability. In addition, the present invention can change the mechanical properties of the microcapsule shell by adjusting the composition and composition ratio of the natural wax, thereby reducing the damage and leakage of the microcapsules caused by friction and wear during the preparation of the paste, so that most of the microcapsules are not damaged during the preparation of the paste, and can ensure that when the microcapsules are used in toothpaste, they can release the active ingredients of the plant glycoside extracts when brushing teeth, thereby playing a role in treating oral ulcers and the like.

[0039] The preparation method of the present invention uses a fluidized bed coating device to prepare well-encapsulated microcapsules, with fast coating speed, high yield, low cost, and a fast and simple preparation method, which can be industrialized for large-scale production. The preparation method adopted by the present invention can also be extended and applied to the microencapsulation of all soluble and high-diffusion active substances, so as to achieve the purpose of isolating the active substances from the external liquid environment and achieving long-term stability, and has important reference value in the fields of medicine, health food and cosmetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a test diagram of the mechanical properties of natural wax mixtures with different ratios in the present invention.

[0041] Figure 2 This is a test image of the surface morphology of the microcapsules containing plant glycoside extracts in Example 1.

[0042] Figure 3 This is a surface morphology diagram of the calcium carbonate toothpaste of the present invention.

[0043] Figure 4 This is a surface morphology diagram of the calcium carbonate toothpaste slurry in the present invention.

[0044] Figure 5 This is a test image of the surface morphology of the microcapsules containing plant glycoside extracts in Example 1.

[0045] Figure 6 This is a surface morphology diagram of the silicon dioxide toothpaste of the present invention.

[0046] Figure 7 This is a surface morphology diagram of the silica toothpaste slurry in the present invention. DETAILED DESCRIPTION

[0047] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0048] The present invention studies the properties of natural waxes of beeswax (W1) and carnauba wax (W3) in different mass percentage ratios, that is, a natural wax mixture containing 5% by mass of W3 (a mixture of W1 and W3, recorded as W1-5%W3), a natural wax mixture containing 10% by mass of W3 (recorded as W1-10%W3), a natural wax mixture containing 15% by mass of W3 (recorded as W1-15%W3), a natural wax mixture containing 20% ​​by mass of W3 (recorded as W1-20%W3), a natural wax mixture containing 30% by mass of W3 (recorded as W1-30%W3), a natural wax mixture containing 40% by mass of W3 (recorded as W1-40%W3), and a natural wax mixture containing 50% by mass of W3 (recorded as W1-50%W3) are prepared respectively, and then the following properties of these natural wax mixtures are tested:

[0049] (1) Mechanical properties

[0050] The hardness and Young's modulus of the natural wax mixture were tested. The specific test results are as follows: Figure 1 As shown, Figure 1 Middle (A) and Figure 1 (B) are the test diagrams of hardness and Young's modulus. Figure 1 It can be seen that when the mass percentage of W3 in natural wax is 5%, the hardness and Young's modulus of W1-5%W3 are 25.06 MPa and 0.41 GPa respectively, and as the content of W3 increases, the hardness and Young's modulus also increase. Since the present invention requires that the shell of the microcapsule can be stably stored in toothpaste and the core material can be released when brushing teeth, comprehensive consideration is taken, when the natural wax is a mixture of beeswax and carnauba wax with a mass ratio of 1: (0.05~0.2), the use requirements of the microcapsule can be met.

[0051] (2) Weight loss rate

[0052] The above natural wax mixture was accelerated stored in calcium carbonate and silica toothpaste at 45°C for 90 days, and then the weight loss rate of the natural wax mixture was tested. The specific test results were as follows: after the above natural wax mixture was accelerated stored in calcium carbonate toothpaste for 90 days, the weight loss rate was 7.37~11.19%, among which W1-15%W3 had the largest weight loss rate, and W1-10%W2 had the smallest weight loss rate. The weight loss rate of accelerated storage for 90 days in silica toothpaste was less than 0.5%. Then, a scanning electron microscope was used to observe the surface morphology of the above natural wax mixture after 90 days of storage. It can be seen that the above natural wax mixture had almost no dissolution phenomenon in silica and calcium carbonate toothpaste, and was in good condition, which could achieve stable encapsulation of plant glycoside extracts.

[0053] The raw materials and testing methods used in the examples and comparative examples of the present invention are as follows:

[0054] The plant glycoside extracts are extracts of Scutellaria baicalensis and Honeysuckle. In the test process of the embodiment, baicalin is used as a marker for testing.

[0055] The preparation method of the plant glycoside extract is as follows: grinding the root of scutellaria baicalensis and honeysuckle into powder, then mixing with ethanol, heating and refluxing extraction at 60-80°C, filtering, drying, and obtaining the extract.

[0056] Baicalin test method: Grind the pellets or microcapsules with a mortar, then accurately weigh 25 mg, record the mass M1, add 20 mL ethanol-phosphoric acid solution (in the ethanol-phosphoric acid solution, the volume ratio of anhydrous ethanol, phosphoric acid and water is 50:6:44), vortex for 2 min, ultrasonically extract in a 25°C water bath for 40 min, centrifuge at 5000 rpm for 10 min, and dilute the supernatant to 25 mL with ethanol-phosphoric acid aqueous solution (in the ethanol-phosphoric acid solution, the volume ratio of anhydrous ethanol, phosphoric acid and water is 50:6:44). Filter with a 0.22 μm filter membrane and take the filtrate as the sample solution. 10 μL was precisely drawn for high performance liquid chromatography, chromatographic conditions: C18 column 250 mm×4.6 mm (particle size 5 μm), column temperature 30°C; mobile phase was acetonitrile and 0.1% phosphoric acid solution, gradient elution (0-2 min: 13% acetonitrile, 87% phosphoric acid solution; 18-25 min: 30% acetonitrile, 70% phosphoric acid solution; 28-30 min, 13% acetonitrile, 87% phosphoric acid solution); flow rate 1.0 mL / min; detection wavelength 277 nm, test and calculate the content of baicalin M2 in the pill core or microcapsule. Drug loading = M2 / M1×100%, where M2 is the content of baicalin in the pill core or microcapsule, and M1 is the mass of the pill core or microcapsule.

[0057] Actual coating weight gain test method: Actual weight gain (%) = (drug loading of pellet core - drug loading in microcapsule) / drug loading in microcapsule × 100%.

[0058] The calcium carbonate toothpaste base formula is as follows: 30% moisturizer, 40% calcium carbonate, 5% hydrated silica, 2% surfactant, 0.8% thickener, 0.2% sweetener, 1.5% fragrance, 0.5% preservative, and the balance is water. The calcium carbonate toothpaste base is obtained by mixing, stirring, homogenizing, and vacuum degassing in a paste making machine.

[0059] The formula of the silicon dioxide toothpaste base is as follows: 45% of moisturizer, 25% of hydrated silica, 2% of surfactant, 0.8% of thickener, 0.2% of sweetener, 1.5% of fragrance, 0.5% of preservative, and the balance of water. The silicon dioxide toothpaste base is obtained by mixing, stirring, homogenizing, and vacuum degassing in a paste making machine.

[0060] Example 1

[0061] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0062] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1:0.05, and 50% of the mass of the dry material was added to make a soft material. A perforated plate with a pore size of 300 μm was selected, the screw extrusion rate was 5 rpm, the spheronization rate was 1500 rpm, and the spheronization time was 20 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0063] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating material was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, the atomization pressure was 0.1MPa, and after coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0064] After testing, the yield of the prepared microcapsules containing plant glycoside extracts was 87.46%, the average particle size of the microcapsules was 376.65 μm, the baicalin loading was 5.62%, and the coating weight gain was 35.29%.

[0065] Example 2

[0066] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0067] Plant glycoside extract, microcrystalline cellulose and carboxymethyl starch were uniformly mixed in a mass ratio of 1:1.25:0.25, and 50% of the mass of the dry material was added to make a soft material. A perforated plate with an aperture of 400 μm was selected, the screw extrusion rate was 5 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0068] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 400 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0069] After testing, the yield of the prepared microcapsules was 83.92%, the average particle size of the microcapsules was 483.53 μm, the baicalin loading was 5.44%, and the coating weight gain was 37.00%.

[0070] Example 3

[0071] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0072] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials were added to make a soft material. A perforated plate with an aperture of 500 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 500 rpm, and the spheronization time was 60 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0073] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0074] After testing, the yield of the prepared microcapsules was 81.56%, the average particle size of the microcapsules was 610.54 μm, the baicalin loading was 5.55%, and the coating weight gain was 37.38%.

[0075] Example 4

[0076] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0077] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.3, and 40% of the mass of dry materials was added to make a soft material. A perforated plate with an aperture of 600 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0078] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 300 rpm, the exhaust speed was 600 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1 MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0079] After testing, the yield of the prepared microcapsules was 78.43%, the average particle size of the microcapsules was 698.24 μm, the baicalin loading was 5.55%, and the coating weight gain was 37.40%.

[0080] Example 5

[0081] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0082] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials were added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 10 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0083] Beeswax and carnauba wax were hot-melted and mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.15 MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0084] After testing, the yield of the prepared microcapsules was 72.45%, the average particle size of the microcapsules was 806.31 μm, the baicalin loading was 5.39%, and the coating weight gain was 39.42%.

[0085] Example 6

[0086] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0087] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials were added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0088] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 150°C, the coating liquid was heated to 110°C, and the atomization pressure was 0.2MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0089] After testing, the yield of the prepared microcapsules was 45.78%, the average particle size of the microcapsules was 816.43 μm, the baicalin loading was 5.65%, and the coating weight gain was 34.65%.

[0090] Example 7

[0091] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0092] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials was added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0093] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.11 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0094] After testing, the yield of the prepared microcapsules was 74.53%, the average particle size of the microcapsules was 818.34 μm, the baicalin loading was 5.62%, and the coating weight gain was 34.56%.

[0095] Example 8

[0096] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0097] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials was added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0098] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.18 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0099] After testing, the yield of the prepared microcapsules was 75.89%, the average particle size of the microcapsules was 806.56 μm, the baicalin loading was 5.69%, and the coating weight gain was 33.52%.

[0100] Example 9

[0101] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0102] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials was added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0103] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.25 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.5. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 190°C, the coating liquid was heated to 140°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0104] After testing, the yield of the prepared microcapsules was 83.52%, the average particle size of the microcapsules was 833.53 μm, the baicalin loading was 5.47%, and the coating weight gain was 39.04%.

[0105] Example 10

[0106] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0107] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials were added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 25 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0108] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.3. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0109] After testing, the yield of the prepared microcapsules was 91.98%, the average particle size of the microcapsules was 776.65 μm, the baicalin loading was 6.22%, and the coating weight gain was 27.07%.

[0110] Embodiment 11

[0111] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0112] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 40% of the mass of dry materials was added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0113] Beeswax and carnauba wax were hot-melted and mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.4. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0114] After testing, the yield of the prepared microcapsules was 81.46%, the average particle size of the microcapsules was 769.32 μm, the baicalin loading was 5.92%, and the coating weight gain was 33.60%.

[0115] Example 12

[0116] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0117] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 50% of the mass of dry materials were added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0118] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.6. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0119] After testing, the yield of the prepared microcapsules was 70.46%, the average particle size of the microcapsules was 845.98 μm, the baicalin loading was 5.25%, and the coating weight gain was 50.48%.

[0120] Embodiment 13

[0121] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0122] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1.25:0.25, and 50% of the mass of dry materials were added to make a soft material. A perforated plate with an aperture of 700 μm was selected, the screw extrusion rate was 8 rpm, the spheronization rate was 800 rpm, and the spheronization time was 30 min to obtain spherical particles, which were dried at 35 ° C and sieved to obtain pellet cores.

[0123] Beeswax and carnauba wax were hot melt mixed at a mass ratio of 1: 0.05 as the coating liquid, and the mass ratio of the pellet core to the coating liquid was 1: 0.7. Tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 170°C, the coating liquid was heated to 130°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0124] After testing, the yield of the prepared microcapsules was 66.41%, the average particle size of the microcapsules was 916.24 μm, the baicalin loading was 5.01%, and the coating weight gain was 57.79%.

[0125] Comparative Example 1

[0126] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0127] Plant glycoside extract, microcrystalline cellulose and cross-linked carboxymethyl cellulose were uniformly mixed in a mass ratio of 1:1:0.05, and 50% of the mass of dry materials were added to make a soft material. A 300 μm pore plate was selected, the screw extrusion rate was 5 rpm, the spheronization rate was 1500 rpm, and the spheronization time was 20 min to obtain spherical particles. The particles were dried at 35 °C and sieved to obtain pellet cores.

[0128] The small tree candle wax was hot melt mixed as the coating liquid, and the mass ratio of the pellet core to the coating material was 1: 0.5. The tangential jet fluidized bed hot melt coating was adopted, the material temperature of the fluidized bed coating machine was controlled at 30°C, the air inlet speed of the coating machine was 600 rpm, the exhaust speed was 1200 rpm, the centrifugal disc speed was 300 rpm, the compressed air temperature was set to 180°C, the coating liquid was heated to 140°C, and the atomization pressure was 0.1MPa. After coating, the microcapsules containing plant glycoside extracts in this example were obtained by sieving.

[0129] After testing, the yield of the prepared microcapsules was 65.56%, the average particle size of the microcapsules was 356.53 μm, the baicalin loading was 5.22%, and the coating weight gain was 30.29%.

[0130] Comparative Example 2

[0131] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0132] (1) Add shellac particles into NaOH solution, stir and heat to 70°C to dissolve. During the dissolution process, add NaOH solution to maintain pH = 7.3 to prepare a shellac solution with a mass concentration of 35%. Add octenyl succinate starch (molecular weight 1.2×10 4 g / mol, degree of substitution is 0.0105), heated at 95℃ for 30min to gelatinize into 35% octenyl succinate starch solution, and adjusted pH = 7.4; added baicalin extract to water and stirred until dissolved to prepare a 35% plant glycoside solution, and adjusted pH = 7.0 with NaOH solution. According to the mass ratio of shellac, octenyl succinate starch and baicalin extract of 1:0.25:0.42, 20g of shellac solution, 5g of octenyl succinate starch solution and 8.33g of baicalin extract solution were mixed and stirred evenly.

[0133] (2) Take 30g of this mixed solution and drip it into 300g of corn oil (the mass ratio of the mixed solution to the vegetable oil is 1:10) at a flow rate of 3.3mL / min, and stir continuously at a speed of 400rpm. After stirring for 30min, slowly add 6.30g of CaCl2 powder in a ratio of CaCl2 to shellac of 1:1, continue stirring and react at a temperature of 25℃ for 4h, and then let it stand for 12h. Centrifuge the reaction system at 4000rpm for 5min and pour off the upper oil. Add n-hexane, centrifuge at 4000r / min for 5min, and repeat washing 3 times. Then rinse the microcapsules with distilled water and filter, and dry at 35℃ for 12h to obtain the microcapsules containing plant glycoside extract in this example, with an average particle size of 136μm.

[0134] Comparative Example 3

[0135] This example provides a microcapsule containing a plant glycoside extract, which is prepared by the following preparation method, and the specific steps are:

[0136] (1) Add shellac particles to NaOH solution, stir and heat to 70°C to dissolve. During the dissolution process, add NaOH solution to maintain pH = 7.4 to prepare a shellac solution with a mass concentration of 35%. Add octenyl succinate starch powder (molecular weight 1.2×10 4 g / mol, degree of substitution is 0.0105), heated at 95℃ for 30min to gelatinize into 35% octenyl succinate starch solution, and adjusted pH = 7.0; added baicalin extract to water and stirred until dissolved to prepare a 35% plant glycoside solution, and adjusted pH = 7.4 with NaOH solution. According to the mass ratio of shellac, octenyl succinate starch and plant glycoside (glycoside) of 1:1:2, 10g shellac solution, 10g octenyl succinate starch solution and 20g plant glycoside (glycoside) solution were mixed and stirred evenly.

[0137] (2) Take 30g of the mixed solution and drip it into 300g of soybean oil (the mass ratio of the mixed solution to the vegetable oil is 1:10) at a flow rate of 3.3mL / min, and stir continuously at a speed of 400rpm. After stirring for 30min, slowly add 2.63g of CaCl2 powder in a ratio of CaCl2 to shellac of 1:1, continue stirring and react at a temperature of 25℃ for 4h, and then let it stand for 12h. Centrifuge the reaction system at 4000rpm for 5min and pour off the upper oil. Add n-hexane, centrifuge at 4000r / min for 5min, and repeat washing 3 times. Then rinse the microcapsules with distilled water and filter, and dry at 35℃ for 12h to obtain the microcapsules containing plant glycoside extract in this example. The average particle size of the microcapsules is 109μm.

[0138] Performance Testing:

[0139] (1) Surface morphology test

[0140] Take 1g of the microcapsules containing plant glycoside extracts prepared in Example 1 and 39g of calcium carbonate toothpaste base and stir at 50 rpm for 1 min to mix evenly to obtain calcium carbonate toothpaste containing microcapsules of plant glycoside extracts; take 1g of the calcium carbonate toothpaste containing microcapsules of plant glycoside extracts, simulate brushing on resin dentures for 3 minutes, keep the intensity of brushing the paste consistent, rinse with water after brushing and collect all the toothpaste slurry. Then, a scanning electron microscope was used to test the surface morphology of the microcapsules containing plant glycoside extracts, calcium carbonate toothpaste and calcium carbonate toothpaste slurry prepared in Example 1. The specific test results are as follows: Figure 2 , Figure 3 and Figure 4 shown.

[0141] Take 1g of the microcapsules containing plant glycoside extracts prepared in Example 1 and stir with 39g of silica toothpaste base at 50rpm for 1 min to mix evenly, to prepare silica toothpaste containing microcapsules of plant glycoside extracts, take 1g of the silica toothpaste containing microcapsules of plant glycoside extracts, and simulate brushing on resin dentures for 3min, keep the intensity of brushing the paste consistent, rinse with water after brushing and collect all the toothpaste slurry. Then, the surface morphology of the microcapsules containing plant glycoside extracts, silica toothpaste and silica toothpaste slurry prepared in Example 1 was tested by scanning electron microscopy, and the specific test results were as follows: Figure 5 , Figure 6 and Figure 7 shown.

[0142] Depend on Figure 2~Figure 7 It can be seen that the microcapsules containing plant glycoside extracts prepared by the present invention are nearly spherical structures with relatively smooth surfaces, and the plant glycoside extracts are encapsulated in the microcapsules. When the microcapsules are mixed and stirred with the toothpaste matrix, the abrasive silica particles or calcium carbonate particles have a wear effect on the surface of the microcapsules, resulting in a reduction in the protective effect of the coating layer of some microcapsules on the ball core. The liquid in the toothpaste enters the interior through the damaged part of the microcapsules or the original loose encapsulation, causing the disintegrant in the ball core to absorb water, swell and disintegrate, which will cause some microcapsules to rupture, but most of the microcapsules are not ruptured and exist stably, proving the stability of the microcapsule structure in the present invention. In addition, after simulating the mechanical action of brushing teeth, most of the microcapsules in the toothpaste rupture, the ball core disintegrates and dissolves, leaving only the "empty shell" formed by the waxy film coating material. By comparing the surface of the waxy film coating layer before and after brushing friction, it can be clearly found that brushing friction makes the wall material surface rougher. After brushing and friction, the rupture of microcapsules in calcium carbonate toothpaste is more serious than that in silica toothpaste, which is caused by the difference in abrasives in the toothpaste system.

[0143] (2) Tests on the leakage rate, release rate and release increment of baicalin

[0144] The microcapsules containing plant glycoside extracts in Examples 1 to 13 and Comparative Example 1 were mixed with a calcium carbonate toothpaste base and a silicon dioxide toothpaste base to prepare calcium carbonate toothpaste containing microcapsules of plant glycoside extracts and silicon dioxide toothpaste containing microcapsules of plant glycoside extracts. The specific preparation method is as follows:

[0145] (1) Preparation of calcium carbonate toothpaste containing microcapsules of plant glycoside extracts: 1 g of the microcapsules containing plant glycoside extracts prepared in Examples 1 to 13 and Comparative Example 1 were respectively mixed with 39 g of calcium carbonate toothpaste base and stirred at 50 rpm for 1 min to obtain a toothpaste.

[0146] (2) Preparation of silica toothpaste containing microcapsules of plant glycoside extracts: 1 g of the microcapsules containing plant glycoside extracts prepared in Examples 1 to 13 and Comparative Example 1 were respectively mixed with 39 g of silica toothpaste base and stirred at 50 rpm for 1 min to obtain a silica toothpaste.

[0147] Then, the leakage of baicalin components in the microcapsules of calcium carbonate toothpaste and silicon dioxide toothpaste containing microcapsules of plant glycoside extract prepared above was tested respectively. The specific test method was as follows: the toothpaste was stored in a sealed glass bottle and placed in a constant temperature oven at 45°C for accelerated storage test. On the 0th day and the 90th day of storage, 1g (precision weighed) of toothpaste was taken and placed in a centrifuge tube, 10g of water was added and allowed to stand for half an hour until the toothpaste was dispersed, and the microcapsules were separated from the toothpaste slurry with a mesh sieve with an aperture of 100μm and collected in a centrifuge tube. The microcapsules were placed in an ethanol-phosphoric acid aqueous solution (the volume ratio of anhydrous ethanol, phosphoric acid and water = 50:6:44), heated at 85°C for 15 min, and the microcapsule wall material was completely melted and the core material was completely dissolved. After rapid cooling to room temperature, vortex oscillation was performed for 2 min, ultrasonic extraction was performed in a 25°C water bath for 40 min, centrifugation was performed at 5000 rpm for 10 min, and the supernatant was fixed to 25 mL with ethanol-phosphoric acid aqueous solution. Filtered with a 0.22 μm filter membrane, the filtrate was taken as the sample solution. The baicalin content was determined by high performance liquid chromatography and the leakage rate of baicalin was calculated.

[0148] .

[0149] The leakage rate data of the baicalin component in the calcium carbonate toothpaste and the silicon dioxide toothpaste measured according to the above test method are recorded in the following Table 1.

[0150] Table 1 Leakage rate of baicalin in calcium carbonate toothpaste and silicon dioxide toothpaste (%, n=3)

[0151]

[0152] As shown in Table 1, compared with Comparative Example 1, the microcapsules containing plant glycoside extracts in Examples 1 to 13 of the present invention are more stable in silicon dioxide toothpaste than in calcium carbonate toothpaste. By comparing Examples 1 to 13, it can be seen that the leakage rate of baicalin decreases with the increase of the size of the pellet core, the increase in the proportion of carnauba wax in the coating material will lead to an increase in the leakage rate of baicalin, and the increase in the coating weight gain will lead to a decrease in the leakage rate of the microcapsules in toothpaste.

[0153] Then, the release rates of the calcium carbonate toothpaste and silicon dioxide toothpaste containing the microcapsules of plant glycoside extract prepared above in the simulated toothbrushing process were tested respectively. The specific test method was as follows: 1 g of toothpaste was taken and brushed on the resin denture for 3 minutes, and the brushing force of the paste was kept consistent. After brushing, rinse with water and collect all the toothpaste slurry. The microcapsules still retained in the toothpaste slurry were separated with a mesh sieve with an aperture of 100 μm, and the retained microcapsules were placed in an ethanol-phosphoric acid aqueous solution (the volume ratio of anhydrous ethanol, phosphoric acid and water = 50:6:44), heated at 85°C for 15 minutes, and the wall material was completely melted and the core material was completely dissolved. After rapid cooling to room temperature, vortex oscillation for 2 minutes, ultrasonic extraction in a 25°C water bath for 40 minutes, centrifugal separation at 5000 rpm for 10 minutes, and the supernatant was fixed to 25 mL with an ethanol-phosphoric acid aqueous solution. Filter with a 0.22 μm filter membrane, and take the filtrate as the sample liquid. The baicalin content was determined by HPLC, and the simulated release rate and toothbrushing release increment were calculated.

[0154] .

[0155] The release rate data of baicalin components in calcium carbonate toothpaste and silicon dioxide toothpaste measured according to the above test method are recorded in the following Table 2.

[0156] Table 2 Simulated release rate and release increment of baicalin in calcium carbonate toothpaste and silicon dioxide toothpaste (%, n=3)

[0157]

[0158] As shown in Table 2, by comparing Examples 1 to 6, it can be seen that the increase in the particle size of the microcapsule containing the plant glycoside extract will increase the brushing release increment of the microcapsule; by comparing Examples 7 to 9, it can be seen that the increase in the proportion of carnauba wax in the coating material will reduce the brushing release increment of the microcapsule containing the plant glycoside extract; by comparing Examples 10 to 13, it can be seen that the reduction in the coating weight gain will increase the brushing release increment of the microcapsule containing the plant glycoside extract.

[0159] (3) Storage stability test of baicalin

[0160] Take 1g of the microcapsules containing plant glycoside extracts prepared in Example 12 and mix them with 39g of silica toothpaste base or 39g of calcium carbonate toothpaste base at 50 rpm for 1 min to obtain silica toothpaste containing microcapsules of plant glycoside extracts and calcium carbonate toothpaste containing microcapsules of plant glycoside extracts as the implementation group. The toothpastes in the implementation group are all microencapsulated plant glycoside extracts. Take an equal amount of plant glycoside extracts and mix them with 39g of silica toothpaste base or 39g of calcium carbonate toothpaste base to mix and stir them evenly as the control group. The toothpaste in the control group is a non-microencapsulated plant glycoside extract. The prepared toothpastes were sealed and placed in a constant temperature oven at 45°C for storage for 3 months. On the 0th, 1st, 5th, 10th, 15th, 30th, 60th and 90th days of accelerated storage, appropriate amounts of silica toothpaste containing microcapsules of plant glycoside extracts and calcium carbonate toothpaste containing microcapsules of plant glycoside extracts were placed in a mortar and ground to completely break the microcapsules. Weigh 1 g (accurate to 0.1 mg) of the ground toothpaste sample in a 50 mL stoppered centrifuge tube, add 1 g of quartz sand and 20 mL of ethanol-phosphoric acid solution (the volume ratio of anhydrous ethanol, phosphoric acid and water is 50:6:44), record the mass, then vortex for 2 minutes, ultrasonically extract in a 25°C water bath for 40 minutes, cool to room temperature, and then use the above ethanol-phosphoric acid solution to make up for the lost mass. Centrifuge at 5000 rpm for 10 minutes, and filter the supernatant with a 0.22 μm filter membrane. The baicalin content was determined by HPLC, and the retention rate of baicalin during different periods of accelerated storage was calculated based on the total baicalin content in 1 g of toothpaste.

[0161] .

[0162] The retention rate data of baicalin in toothpaste of the implementation group and the control group measured according to the above test method are shown in Table 3 below.

[0163] Table 3 Retention rate of baicalin in toothpaste during accelerated storage at 45℃ (%, n=3)

[0164]

[0165] As shown in Table 3, in calcium carbonate toothpaste and silicon dioxide toothpaste, microencapsulation increased the retention rate of baicalin after accelerated storage for 90 days by 43.32% and 24.11% compared with the control group, proving that microencapsulation helps retain baicalin during toothpaste storage.

[0166] 1 g of the microcapsules containing plant glycoside extracts prepared in Comparative Examples 2-3 were taken and mixed with 39 g of silica toothpaste base at 50 rpm for 1 min to obtain silica toothpaste containing microcapsules of plant glycoside extracts. The prepared toothpastes were sealed and placed in a constant temperature oven at 45°C for 1 month. On the 0th, 2nd, 4th, 7th, 10th, 20th and 30th days of the accelerated storage process, appropriate amounts of silica toothpaste samples containing microcapsules of plant glycoside extracts were taken and placed in a mortar and ground to completely break the microcapsules. Weigh 1 g (accurate to 0.1 mg) of the ground toothpaste sample in a 50 mL stoppered centrifuge tube, add 1 g of quartz sand and 20 mL of ethanol-phosphoric acid solution (the volume ratio of anhydrous ethanol, phosphoric acid and water is 50:6:44), record the mass, then vortex for 2 min, ultrasonically extract in a 25 ° C water bath for 40 min, cool to room temperature, and then use the above ethanol-phosphoric acid solution to make up for the lost mass. Centrifuge at 5000 rpm for 10 min, and filter the supernatant with a 0.22 μm filter membrane. The baicalin content was determined by high performance liquid chromatography, and the leakage rate of baicalin at different periods of accelerated storage was calculated based on the total baicalin content in 1 g of toothpaste. The leakage rate data of baicalin in toothpaste of Comparative Examples 2-3 measured according to the above test method are shown in Table 4 below.

[0167] Table 4 Leakage rate of baicalin in toothpaste of comparative examples 2 to 3

[0168]

[0169] As shown in Table 4, the microcapsules in Comparative Examples 2-3 have a leakage rate of baicalin exceeding 90% after accelerated storage in silica toothpaste for 30 days, and the storage stability is significantly lower than that of the microcapsules in the present invention. The reason is that the water content in silica toothpaste is relatively high, and the content of hydrophilic components such as humectants is much higher than that in calcium carbonate toothpaste. The microcapsules in Comparative Examples 2-3 have poor resistance to hydrophilic components and have a high leakage rate in silica toothpaste. However, the retention rate of the microcapsules in the present invention is still more than 70% after accelerated storage for 90 days, that is, the leakage rate is not higher than 30%. Therefore, the microcapsules in the present invention have a good resistance to hydrophilic components in both silica toothpaste and calcium carbonate toothpaste, and have excellent storage stability.

[0170] (4) Oral ulcer treatment effect test

[0171] Oral ulcer model was established in SPF SD rats of about 6 weeks old and weighing 230-250 g. After anesthesia, filter paper with a diameter of 0.4 mm was soaked in 50% NaOH solution and pressed on the oral palate mucosa to establish ulcer model. The animals with oral ulcer model were divided into model control group, positive control group and experimental group. The model control group was coated with physiological saline; the positive group used watermelon frost as a positive control; the experimental group was divided into microcapsule group and non-microencapsulated group, wherein the microencapsulated group was a mixture of 1 g of microcapsules containing plant glycoside extract obtained in Example 12 and 39 g of calcium carbonate toothpaste base, and the non-microencapsulated group was a mixture of 0.2 g of plant glycoside extract powder and 30.15 g of calcium carbonate toothpaste base. The content of baicalin in the toothpaste of the microcapsule group and the non-microencapsulated group was consistent. After the two groups of experimental toothpastes were subjected to 45°C accelerated storage experiment for 0 days, 60 days and 90 days, the rat oral ulcer healing experiment was carried out.

[0172] The drug administration started 24 hours after modeling. After the animals in each drug administration group were anesthetized with isoflurane, 0.2 g of the corresponding toothpaste was applied to the ulcer in each experimental group. The toothpaste in the microcapsule group was completely ground and crushed with a mortar before administration; the positive control group was applied with 0.03 g of watermelon frost; the model control group was applied with normal saline; after keeping it for 3 minutes, the test substance was wiped off. The drug administration and application frequency were 2 times / day, once at a fixed time in the morning and afternoon, for 8 consecutive days. During this period, the diameter of the ulcer surface was measured, the ulcer area was calculated, and the healing rate of oral ulcers was calculated according to the change in the ulcer area. The oral ulcer healing rate data of rats measured according to the above test method are shown in Table 5 below.

[0173] Table 5 Oral ulcer healing rate in rats

[0174]

[0175] As shown in Table 5, compared with directly adding plant glycoside extracts into toothpaste, microencapsulation can ensure that the glycoside active ingredients still have a good effect in promoting the healing of oral ulcers after accelerated storage in toothpaste.

[0176] In summary, the present invention uses natural wax as a coating material to encapsulate plant glycoside extracts to form microcapsules. The surface of the microcapsules is smooth and the encapsulation is dense, which improves the stability of glycoside substances, avoids unstable phenomena such as oxidation and decomposition, improves the stability of plant glycoside extracts in toothpaste, and makes the toothpaste containing the microcapsules have a longer storage stability. In addition, by adjusting the composition and composition ratio of natural wax, the present invention can change the mechanical properties of the microcapsule shell, thereby reducing the damage and leakage of the microcapsules caused by friction and wear during the preparation of the paste, so that most of the microcapsules are not damaged during the preparation of the paste, and can ensure that when the microcapsules are used in toothpaste, they can release the active ingredients of the plant glycoside extracts when brushing teeth, thereby playing a role in treating oral ulcers.

[0177] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A microcapsule, characterized in that: The microcapsule is a core-shell structure, the shell of the microcapsule is natural wax; the core of the microcapsule includes a plant glycoside extract; the mass ratio of the core of the microcapsule to the shell of the microcapsule is 1:(0.3-0.7); the natural wax is a mixture of beeswax and carnauba wax in a mass ratio of 1:(0.05-0.2).

2. The microcapsule according to claim 1, characterized in that: The raw material of the plant glycoside extract is selected from at least one of scutellaria baicalensis, honeysuckle, coptis chinensis, liquorice, fritillaria thunbergii, perilla frutescens, patchouli, tangerine peel, dried ginger, jujube, anemarrhena asphodeloides, phellodendron chinense, moutan bark, raw rehmannia root and ophiopogon japonicus.

3. The microcapsule according to claim 1, characterized in that: The inner core of the microcapsule also includes a filler and a disintegrant; the mass ratio of the plant glycoside extract, the filler and the disintegrant is 1: (1-1.25): (0.05-0.3).

4. The microcapsule according to claim 3, characterized in that: The disintegrant is selected from at least one of cross-linked carboxymethyl cellulose and carboxymethyl starch; And / or, the filler is selected from microcrystalline cellulose.

5. The microcapsule according to any one of claims 1 to 4, characterized in that: The particle size of the microcapsule is 370-920 μm; and / or, the content of baicalin in the microcapsule is 5-6.3%; And / or, the coating weight gain in the microcapsule is 27.07% to 57.79%.

6. The method for preparing the microcapsule according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: making the core material of the microcapsule into a pellet core; S2: coating the pellet core with natural wax to obtain the microcapsule.

7. The method for preparing microcapsules according to claim 6, characterized in that: The particle size of the pellet core is 0.3-0.7 mm.

8. A toothpaste, characterized in that: The microcapsule comprises the microcapsule according to any one of claims 1 to 5.

9. Use of the microcapsule according to any one of claims 1 to 5 in the preparation of oral care products.

Citation Information

Patent Citations

  • Encapsulates

    CN102906238A

  • Oral care composition

    WO2008015186A1

  • Compositions comprising ph-sensitive microcapsules

    WO2019117890A1

  • Water capsule for cigarettes using compound salts as wall material and preparation method thereof

    CN104479870A

  • Pseudoephedrine slow release pellets and preparation method thereof

    CN109966265A